Uso de los residuos del cultivo de maíz (Zea Mays), como alternativa sostenible para la elaboración de bloques, parroquia Boyacá. - Domínguez Arteaga, Sonia Guadalupe (2018)
The purpose of this research was to evaluate the use of corn crop residues (Zea mays) as a sustainable alternative in the production of blocks for construction. For the development of this experimental work a survey was applied to the producers of the corn crop in the parish of Boyaca, Chone, in order to know the final destination of this waste. The results of the survey revealed that 73% open-pit burn corn crop residues after each harvest period, 20% use it as feed for livestock, 5% silage and 2% reuse it as a fertilizer for the plants. To obtain the blocks, three treatments and a control were established, with different dosages of corn crop residues (corncob, stem and leaf): T1 (25% - 1,25 kg); T2 (50% - 2,50 kg); T3 (75% - 3,75 kg) and control (100% - 5 kg). Then comprehension resistance tests were carried out at 7, 14, 21 and 28 days in order to compare them with the traditional blocks. Finally, as a result it was obtained that the T1 with 25% of residues of the corn crop presented the highest resistance (43 kg/cm2) at 28 days, which allowed to conclude that this block complies with the parameters of the NTE INEN 3066 standard (2016) classifying it as a block for class B construction. According to the statistical analysis, there are significant differences between each of the treatments.